Implementasi Kebijakan Pelayanan E-KTP Di Kecamatan Singkil Kota Manado - LANTI, YUNIAR (JURNAL ADMINISTRASI PUBLIK, 2014)
Abstrak :Subdistrict Singkil is one of the districts located in the region of Manado North Sulawesi province. The total area of the District Singkil is 386.4 ha, which consists of nine villages and forty-eight environments. Singkil subdistrict has a population of Â± 60 272 people, made up darilaki 30,412 men and women 29 860 soul spirit, soul and compulsory ID cards 44,837 18,301 heads of household life. The implementation of e-ID card service policies in Singkil District of Manado City in general has been effectively seen in four important aspects of the policy implementation process as proposed by Edward III, namely: (1) communication: communication that occurs in the implementation of e-ID card service policies in the District Singkil Manado has been implemented in accordance with what is set, the instruction or command leadership to the staff of the e-ID card service program in the district of Singkil is clear, the information provided leadership to the executive employees are clear and easily understood by staff / employees implementers, as well as methods of implementation clear and easily understood by the public, (2) the resources, in terms of the number of executive staff, information / knowledge held by employees of executive, budget, and facilities supporting the implementation of the e-ID card program, everything is good and adequate, (3 ) disposition, judging from the support of this program, the priority of this program, competency, commitment executor, and the role of leadership in funding for implementing an employee incentive, showing disposition of this program is good, all the elements / components of the government in supporting the implementation of this program. (4) The structure of the bureaucracy, as the structure of the implementing organization / division of labor, standard operational procedures (SOP), the mechanism of service procedures, as well as the standard completion time implementation of e-ID card program in the District Singkil is good and in accordance with the instructions of the implementation.Keyword : implementation of policy, service